Identification of outliers in a one-way random effects model - Jürgen Wellmann; Ursula Gather (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2000)
We distinguish between three types of outliers in a one-way random effects model. These are formally described in terms of their position relative to the main part of the observations. We propose simple rules for identifying such outliers and give an example which involves median-based statistics.
Keywords: 519; mixed linear model variance components; random effects; robust statistics; median; median absolute deviation